Investigation on the Relation between the Level of Wind and PV Generation and the Contracted and Mobilized FRR and RR Reserves in Portugal - João Tomé Saraiva (2019)
The Portuguese generation system includes a large amount of wind parks plus a rapidly increasing capacity in PV units. These units as well as some other technologies are classified as Special Regime Generation, SRG, and are paid feed in tariffs. The operation planning for the next day is based on estimates of these injections made in the morning of the day before operation. Then on the operation day, the wind and PV generations will likely be different originating the activation of reserves, namely automatic Frequency Restoration Reserve, aFRR, and Replacement Reserve, RR. Therefore, the main purpose of this paper is to report the research that was conducted to check whether the large amount of wind and PV capacities explain the amounts of contracted and mobilized aFRR and RR reserves. To do this we used data for 2016 publicly available on the web page of the Portuguese TSO. The clarification of this issue is relevant because the amount of money required to pay reserves has been increasing in recent years and this amount is internalized in the Access Tariffs paid by all Portuguese consumers. (c) 2019 IEEE.